The measurement and analysis of surface geometric structure of ceramic femoral heads. Issue 1 (26th June 2013) - Niemczewska‐Wójcik, M.; Gawlik, J.; Sładek, J.; Brown, Christopher A.
Summary The surface functionality of interacting components is determined by evaluating geometric surface structure. Hence, the ceramic femoral heads originated from precision machining were subject to measurement and analysis with regard to roughness, surface damages and deviation from roundness. A variety of measurement techniques were applied in order to thoroughly examine the product quality. The obtained results proved in accordance with the specification: Ra was not greater than 0.05 µm, whereas Δ was less than 10 µm (5 µm) when ceramic balls were used in conjunction with a polyethylene (ceramic) socket. Additionally, the surface damages which can affect the life of a friction pair were analyzed. SCANNING 36:105–114, 2014. © 2013 Wiley Periodicals, Inc.